High-Sensitivity Liquid Level Sensor Based on the Balloon-Shaped Fiber Optic MZI - Tutao Wang; Bo Liu; Lilong Zhao; Yaya Mao; Jianxin Ren; Jiewen Zheng (IEEE Photonics Journal, 2022)
We demonstrated a high-sensitivity liquid level sensor based on the balloon-shaped fiber Mach-Zehnder interferometer (MZI). To make an optical fiber MZI sensor, a bare single mode fiber (SMF) is bent into a balloon shape. The sensor is attached to a stiff support and linked to a buoyancy ball floating on the liquid surface via a thin thread. The change in liquid level will bend the fiber and lead to a wavelength shift of transmission spectrum. This is a novel method of measuring liquid levels. We comprehensively studied the sensing performance of the sensor, and applied the ridge regression algorithm to optimize the fitting results of the experimental data. The maximum sensitivity of liquid level and temperature are 5.245 nm/mm and 40.3 pm/°C respectively, and the sensor has a low temperature cross-sensitivity of 0.00768 mm/°C. Furthermore, the sensor has the advantages of real-time response, convenient manufacture, low cost and high reliability, which broadens the application area of balloon-shaped MZI and makes it appropriate for liquid level sensing.